Open Innovation Adoption and Performance in SMEs: A LISREL Analysis of the Case of Morocco - Ahsina, Khalifa; Jaafar, Adraa; Bennani, Zakaria; Mchiche, Rachid (European Public & Social Innovation Review, 2025)
Introduction: Open innovation is crucial for business competitiveness (Chesbrough, 2003). As companies face internal resource constraints, they turn to collaborative approaches to drive innovation. However, most research focuses on large firms, leaving a gap in understanding open innovation in Moroccan SMEs. This article examines the key factors influencing its adoption and its impact on SME performance. Methodology: A survey was conducted among 99 Moroccan SMEs using self-administered questionnaires via Google Forms. The collected data was analyzed using structural equation modeling, specifically the LISREL method. Results: Findings indicate that the adoption of open innovation is influenced by several factors, including knowledge of the concept, company size and age, ownership structure, strategy, and internationalization. Discussion : A positive correlation emerges between open innovation and SME performance improvement. SMEs perceive it as a means to strengthen their innovation processes and reputation, despite resource limitations. Conclusion: Open innovation presents a key opportunity for Moroccan SMEs. Its implementation enables them to overcome constraints and enhance their competitiveness.